Characteristics of episodic breathlessness as reported by patients with advanced chronic obstructive pulmonary disease and lung cancer: Results of a descriptive cohort study. (May 2015) - Weingärtner, Vera; Scheve, Christine; Gerdes, Verena; Schwarz-Eywill, Michael; Prenzel, Regina; Otremba, Burkhard; Mühlenbrock, Juliane; Bausewein, Claudia; Higginson, Irene J; Voltz, Raymond; Herich, Lena; Simon, Steffen T
Background: Episodic breathlessness is one form of refractory breathlessness. Better understanding of the symptom is necessary for effective management. Aim: The aim was to describe the characteristics of episodic breathlessness in patients with advanced chronic obstructive pulmonary disease or lung cancer. Design: This is a longitudinal cohort study. Outcomes were assessed monthly by up to 13 telephone interviews: peak severity (modified Borg scale: 0–10), duration, frequency, and timing of breathlessness episodes. Data from each episode were pooled and analyzed using descriptive statistics. Associations between outcomes were explored by correlation coefficients. Setting/participants: Patients with chronic obstructive pulmonary disease (Global Initiative for Chronic Obstructive Lung Disease classification stage III or IV) or primary lung cancer (any stage) were recruited in two inpatient units (internal medicine) and two outpatient clinics in Oldenburg, Germany. Results: A total of 82 patients (50 chronic obstructive pulmonary disease, 32 lung cancer), mean age (standard deviation) 67 years (8 years) and 36% female, were included reporting on 592 breathlessness episodes (chronic obstructive pulmonary disease: 403, lung cancer: 189). Peak severity was perceived significantly higher in chronic obstructive pulmonary disease patients than in lung cancer patients (mean (standard deviation) Borg scale: 6.2 (2.1) vs 4.2 (1.9); p  < 0.001). Episodes described by chronic obstructive pulmonary disease patients were longer than those described by lung cancer patients (median (range): 7 min (0–600) vs 5 min (0.3–120), p  = 0.002)). Frequency was similar and most often daily in both groups. Severity and frequency of episodes were correlated in lung cancer patients (r = 0.324, p  = 0.009). Conclusion: Most breathlessness episodes are short (minutes) and severe with significant differences between chronic obstructive pulmonary disease and lung cancer patients. Effective management strategies are warranted to improve symptom relief and coping.